A viabilidade da agricultura familiar: formas de organização produtiva no Oeste do Paraná - Stoffel, Jaime Antonio (2004)
The objective of this study is to comparatively analyse the socio-economic performance reached by different kinds of productive organizations of the small family agricultural production in the west of Paraná in order to determine which kinds present bigger or shorter viability to the development of the family agriculture in that region With the development of capitalism in the country there was a growing transformation in that region and a consequently diversity of the kinds of productive organizations with implications for the viability and the socio-economic performance of those kinds of small producers So at least four kinds of productive organizations of the small family agricultural production appeared and developed in the decades of 1970 and 1980 in that region and are still predominant: a) Productive organization with prevailing integrated production; b) Productive organization with prevailing farming diversification; c) Productive organization with production exclusively agricultural; and d) Productive organization with prevailing agricultural production This way in terms of work hypothesis we found out the socio-economic viability of the small family agricultural production is related to its kind of productive organization By studying primary and secondary data it could be concluded that the relationship exists but not in simple kind This study points out that each different kind of productive organization presents different potentialities and obstacles to its viability which is justified by the different combinations of activities performed in the small family production in that region determining bigger or shorter socio-economic performance This way we can?t suggest a single destiny to the small family production in that region since its destiny depends on its own inside production factors available in the small properties especially labor and natural resources and also outside factors which coerce into its behaviour